2018
DOI: 10.3390/foods7120201
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of 18 Polycyclic Aromatic Hydrocarbons in Daily Foods (Hanoi Metropolitan Area) by Gas Chromatography–Tandem Mass Spectrometry

Abstract: Polycyclic aromatic hydrocarbons (PAHs)—a large group of organic compounds—are extremely hazardous to human health. In this study, the 198 samples from six groups of daily food products in the Hanoi metropolitan area were collected and prepared by the QuEChERS sample treatment technique. The detection and identification of PAHs were obtained by gas chromatography–tandem mass spectrometry (GC–MS/MS) determination. The results demonstrated that the recovery of PAH compounds ranged approximately between 71% and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Studies in Doha, Qatar showed after analysing smoked meat samples, there were none that exceeded European Commission's maximum limits, EC 835/2011 (Hussain et al, 2018). However, similar research undertaken by Tran-Lam et al (2018) in Vietnam revealed thus: the ranges of average PAHs levels were 9.3-9.6 µg/kg (for instant noodles), 0.22-2.48 µg/kg (for cakes) 0.91-4.83 µg/kg (dried vegetables), 5.14-23.32 µg/kg (teas), 4.82-24.35 µg/kg (coffees), and 1.43-25.2 µg/kg (grilled meats). The results indicated that the total concentrations of residual PAHs and benzo(a)pyrene in the instant noodles and grilled meat samples surpassed the maximum limits tolerated by the European Commission (35 µg/kg and 5 µg/kg, respectively) in many investigated samples.…”
Section: Occurrence Of Pahs In Foodmentioning
confidence: 54%
See 1 more Smart Citation
“…Studies in Doha, Qatar showed after analysing smoked meat samples, there were none that exceeded European Commission's maximum limits, EC 835/2011 (Hussain et al, 2018). However, similar research undertaken by Tran-Lam et al (2018) in Vietnam revealed thus: the ranges of average PAHs levels were 9.3-9.6 µg/kg (for instant noodles), 0.22-2.48 µg/kg (for cakes) 0.91-4.83 µg/kg (dried vegetables), 5.14-23.32 µg/kg (teas), 4.82-24.35 µg/kg (coffees), and 1.43-25.2 µg/kg (grilled meats). The results indicated that the total concentrations of residual PAHs and benzo(a)pyrene in the instant noodles and grilled meat samples surpassed the maximum limits tolerated by the European Commission (35 µg/kg and 5 µg/kg, respectively) in many investigated samples.…”
Section: Occurrence Of Pahs In Foodmentioning
confidence: 54%
“…They are pollutants that can be generated during processing food and are ubiquitous (Li et al, 2020). PAHs in the atmosphere can react with other pollutants such as sulphur dioxide, nitrogen oxides and ozone forming dinitro-PAHs, nitro-, diones, and sulfonic acids (Tran-Lam et al, 2018). PAHs may also be degraded by some microorganisms in the soil (Salman and Kadhim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are also several GC-FID and GC–MS methods developed for PAH analysis in mixed varieties of food matrices including grilled meats, rice, noodle, cake, dried vegetable, tapioca flour, corn flour, orange juice, apple juice, tea, coffee and water. In a study dealing with analysis of 18 PAHs in 6 different food types, Tran-Lam et al [ 44 ] reported that a QuEChERS method coupled with GC–MS/MS by using acetonitrile as the extraction solvent, 4 gMgSO 4 and 1 g NaCl as the extraction powder and 0.9 g MgSO 4 /0.3 g PSA/0.3 g C18 as the purification powder for subsequent separation in a DB-5MS capillary column (30m × 0.25 mm, film thickness 0.25 μm) with helium gas at 1 mL/min and detection in electron ionization mode with GC–MS interface temperature at 310 °C. A total of 18 PAHs including 16 EPA priority PAHs, 1-methylnaphthalene (mNAP1) and 2-methylnaphthalene (mNAP2) were separated within 45 min with the validation parameters LOD, LOQ and recovery being from 0.01 to 0.20 ng/g, 0.03–0.60 ng/g and 71–101%, respectively.…”
Section: Chromatographic Methods For Pah Analysismentioning
confidence: 99%
“…The PAHs were analysed using GC-MS (Agilent Technologies GC system 7890B/Agilent Technologies GC Sampler 80/GC-MS Triple Quad 7000C) with High-Efficiency DB-5ms Ultra Inert GC Column under standard chromatographic conditions defined in existing Agilent application notes. 42 Quality Control (QC) samples were spiked with 30 μL of 0.1 μg/ml of an internal standard containing a mixture of 18 PAH congeners (PAH-Mix 45 by Dr Ehrenstorfer GmBH) to yield QC similar to that in Tran-Lam et al 43 . These quality control samples were taken through the same processes of extraction and purification as the test samples.…”
Section: Pahs Extraction and Analysesmentioning
confidence: 99%